Teaching Reading by Using Skimming and Scanning Technique to Improve Studentsâ Reading Skill onrd Semester at the University of Tujuh Belas Agustus 1945 Banyuwangi in Academic Year 2015-2016 - *, Hastowoadi (Sebelas Maret University, 2016)
Nowadays, Reading is an activity which need deeper concentration to sweep all information through textual.There are many reasons why getting student to read is a very important part of lecturerâs job.Â Many students wantto be able to read the text either for their career, for study or pleasure. Reading is useful for language acquisitionprovided that students more or less understand of what they read.Â More they read is absolutely help them to getbetter. Reading is also one of many ways to help them to improve their vocabulary knowledge. The effectivenessin reading is the key of mastery the skill well; through skimming and scanning method. To run out this methodwell, students should know the steps how to use skimming and scanning method in order to understand a textbook. Skimming is the process to get an idea of the whole passages or to sweep all text book to get the topic oridea. Besides, scanning means searching for particular information to answer quickly and directly in a fewminutes. As an international language, English should be comprehended by thousand people, especially forstudents of English Department at university. In fact, they have less understanding in reading skill. It can beshown from their reading test reach less than 0,6-0,8 in validity and 0,4-0,7 in reliability or about 60 percent ofstudents get below the standard of reading achievement. According to the problem, the researcher tries to run outClass Action Research through skimming and scanning method and it has been got that their reading skill raisesignificantly through 2 cycles process.